The Motivation as A Mediation Relationship of Work Load Performance in Medical Record Staff at X Hospital - Febby Ferava; Rina Anindita; M. Reza Hilmy (Penerbit Kemala Indonesia, 2021)
The rapid development of medical science and technology has improved socio-economic and educational conditions. Here, they condition had resulted in changes to the public assessment system which is demands of quality health services. The one of parameters for determining a quality of health services in a hospital is data or information from medical records. In medical record services, a human resource (staff) is required to carry out their duties and responsibilities in recording patient status properly and correctly. Here, the level of workload medical staff there have mistaken taking medical records until they are not found due to important effect on staff performance and motivation. Thus, in this study aimed to analyse the effect of workload on the performance of outpatient medical records with work motivation as an intervening variable in the hospital. This study we use quantitative data in the medical record unit at X Hospital. The unit of analysis is an individual employee in the medical record. The analysis Data are used path analysis with multiple regression analysis. The results show the indicate workload and performance have a significant effect on work motivation. Workload has a significant effect on work motivation. Work motivation has a significant effect on performance. Workload does not have a significant effect on performance. The research findings show that workload does not have a direct effect on employee performance, but workload can affect performance through work motivation because workload has a significant effect on work motivation and work motivation has a significant effect on employee performance with 0.678 of R2 value. The motivation given to the respondent's answer shows extrinsic factors that play a role in the form of providing salaries and rewards for staff / employees at the hospital.